CRIMINAL COOKING OIL HOOKING IN INDONESIA - Junaedi Junaedi (International Journal of Social Science, 2022)
The rules regarding criminal sanctions for hoarders (cooking oil) of Cooking Oil in Indonesia have been regulated in Article 107 of Law (UU) Number 7 of 2014 concerning Trade and Presidential Regulation Number 71 of 2015 concerning Stipulation and Storage of Basic Necessities and Goods. This data analysis was carried out using an analysis based on the Criminal Hoarding of Cooking Oil in Indonesia. The purpose of this research is to be able to examine and analyze the Criminal Hoarding of Cooking Oil in Indonesia. As for the benefits of this research academically, this research is useful related to the crime of hoarding cooking oil in Indonesia, while theoretically, this research can enrich the literature in terms of studying the crime of hoarding cooking oil in Indonesia.